Productivity Analysis of Eggs Production in Khorasan Razavi Province, Iran - Mohaddes, S.A. (International Journal of Poultry Science, 2009)
Egg production is one of the most important agricultural economic activities in Iran. According to the latest information in Iran, there were about 1432 poultry eggs farms producing about 576478 tons of edible eggs in 2005. The poultry farmers, however, complained that the cost of production was very high and that failed to gain considerable profit from their farming operations. The consumers, on the other hand, protested that the poultry price was very high. The purpose of this study is to determine the productivity level of the industry so that a more sustainable and high productivity production system can be developed. Production function was used to measure productivity. A transcendental production function was estimated using cross-sectional data collected from 47 farmers in the Khorasan Razavi province. Secondary data from the Iranian Statistical Year Book (published by the Statistical Center of Iran) were also used. The results of the study found that the cost-benefit ratio was 0.96. The Average Product (AP), Marginal Product (MP), Value Marginal Product (VMP), Optimal Allocation Ratio and the Elasticity of Production (EP) of the feed input were 0.41, 0.16, 577 Rials, 0.48 and 41% respectively. The findings for similar measures above for pullet input were 18.38, 4.24, 14826 Rials, 1.23 and 0.23 respectively. From the study, the average productivity of the poultry farm was 1.04. This shows that the income approximately equals the variable cost. When the fixed costs were taken into consideration, the profit of the average farm was negative. The results indicated that farmers were using feed more than “the optimal level ” and that they were using pullet less than “the optimal level. ” Therefore, to improve profitability, they should use less feed and keep more pullets. In this manner, the cost of production can be reduced.